CRITERIA AND METHODS FOR ANALYZING ARCHITECTURAL AND PLANNING SOLUTIONS IN LOW-RISE INDIVIDUAL HOUSING DEVELOPMENT - Kutryk, Nazar (Theory and practice of design, 2025)
Purpose. The aim of the article is to develop a systematic approach to the assessment of the architectural and planning environment of single-family residential developments, taking into account modern requirements for comfort, energy efficiency, and aesthetic quality of space. Methodology. The methodological basis includes analytical, comparative, and systematization methods aimed at summarizing regulatory frameworks, analyzing scientific sources, and practical examples of low-rise residential design. The study applies principles of functional-spatial analysis, environmental approach, and criteria-based evaluation of architectural solutions. Results. The main factors influencing the quality of the residential environment were identified: orientation and solar exposure of buildings, hygienic parameters of the land plot, functional and technical characteristics, economic efficiency, and architectural-artistic expressiveness. A set of criteria for assessing the architectural and planning environment was developed, which can serve as a methodological tool in design practice. Scientific novelty. The scientific novelty lies in the systematization and integration of various approaches to residential environment assessment into a unified criteria-based model adapted to the conditions of low-rise development in Ukrainian cities. A refined structure of criteria is proposed, combining technica-economic, ecological, and aesthetic aspects of architectural design. Practical relevance. The obtained results can be applied in design organizations, during the development of regulatory documents, in the educational process of architectural specialties, and in the evaluation of the quality of low-rise residential complexes. The proposed criteria contribute to increasing the efficiency of design solutions and improving the quality of the residential environment.